(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article explores the linkages between regional strategies for the social economy and regional development in Uzbekistan. It provides a comparative perspective of regional strategies for the social economy, based on: the level of recognition of the social economy itself, multi-level governance arrangements, the regional strategic priority given to the social economy and financial resources available for regional strategies. It gives examples of strategies for the social economy in selected regions in the four countries to document the diversity of practice. It outlines conclusions and policy orientations to help reinforce the positive impact of regional strategies for the social economy on regional development.